A FLOW OF WEALTH: WASTEWATER DISPOSAL IN REPUBLICAN TIANJIN. Issue 2 (3rd August 2018) - Mu, Cao
ABSTRACT: Tianjin is the largest port city in Northern China and a major hub for water and land transportation. For geological reasons, the city has long been troubled by water drainage problems. To remove wastewater from within its walls, the city developed a drain system which relies on human labor and a series of variously sized ditches. Unlike the modern sewage system, which simply discharges wastewater into surrounding rivers and the sea, Tianjin's traditional wastewater disposal system worked in concert with an urban manure collection system. Urban wastewater was recycled as fertilizer, a valuable resource for the surrounding rural area. In tracing the origin, evolution, and influence of urban wastewater disposal in Tianjin, this article aims to reveal the potential value in Chinese traditional waste management practices. Contemporary urban waste disposal systems might benefit from a better understanding of the relationship between urban and rural areas that characterized these traditional practices.